On Subclasses of Uniformly Spiral-like Functions Associated with Generalized Bessel Functions. (20th August 2019) - Frasin, B. A.; Aldawish, Ibtisam
Abstract : The main object of this paper is to find necessary and sufficient conditions for generalized Bessel functions of first kindz u p ( z ) to be in the classesS P p ( α, β ) andU C S P ( α, β ) of uniformly spiral-like functions and also give necessary and sufficient conditions forz ( 2 - u p ( z ) ) to be in the above classes. Furthermore, we give necessary and sufficient conditions forI ( κ, c ) f to be inU C S P T ( α, β ) provided that the functionf is in the classR τ ( A, B ) . Finally, we give conditions for the integral operatorG ( κ, c, z ) = ∫ 0 z ( 2 - u p ( t ) ) d t to be in the classU C S P T ( α, β ) . Several corollaries and consequences of the main results are also considered.